PERKEMBANGAN PENGATURAN JAMINAN SOSIAL TENAGA KERJA DALAM RANGKA PERLINDUNGAN HUKUM BURUH/PEKERJA - dede agus (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
Each worker/workers face the risks of social-economic and social security can cope with the risks of the socio-economic. Setting social security law for labors has been started since the days of the Dutch East Indies colonial rule until the time of independence of the Republic of Indonesia both early era of independence as well as in the reform era. Therefore, this paper intends to study the development of legal regulation of social security. Social security arrangements colonial era the Netherlands East Indies, set in the Civil Code and Regulations Accident or Ongevallen-Regelling 1939, but the laborers / workers unprotected. New on the independence of the Republic of Indonesia, especially after the enactment of legislation in the field of social security such as: Law Number 3 of 1992 on Social Security of Labor, Law 20 of 2004 on National Social Security System and the Law 24 of 2011 on Social Security Organizing Body, laborers / workers obtain legal protection in the field of social security, which programnyapun not only guarantees compensation for workplace accidents alone, but includes work accident insurance program, program life insurance, security program today old, pension insurance programs, and health care insurance program. Keywords: Social Security Labor Protection Law, the Labour / Workers, Development, Settings.